A novel improved flooding algorithm for DSR protocol in MANET - Peili CONG; Heng ZHAO (Dianxin kexue)
In mobile Ad Hoc network（MANET）,based on the geographical location of mobile nodes,a novel improved location- based flooding algorithm（ILFA）was proposed, which controlled network traffic effectively by rebroadcast routing packets according to geographical location. In additional, ILFA was also applied in the traditional dynamic source routing（DSR）protocol, which restricted the search range of routing discovery according to define request area and expected area, and then limited the RREQ rebroadcast range by assigning a nominated neighbors to rebroadcast RREQ （NNRR）list, in order to eliminate the number of rebroadcast RREQ of DSR. The simulation results demonstrate that, compared to the traditional flooding algorithm, ILFA can reduce the network overhead and improve the network throughput efficiently.